Структурное состояние мембранных белков эритроцитов человека при взаимодействии с лигандами β1-адренорецепторов — добутамином и атенололом - Жирнов, В.В.; Хижняк, С.В.; Войцицкий, В.М.; Лапоша, Е.А. (Видавничий дім "Академперіодика" НАН України, 2008)
Interaction of β1-adrenoreceptor ligands, dobutamine and atenolol, with human erythrocyte membranes by acrylamide quenching the intinsic protein fluorescence has been investigated. It is shown that, by binding with membranes, these ligands form protein conformations having different efficiencies and availabilities for the quenching by acrylamide. The findings allow us to assume that atenolol is an inversion antagonist of human β1-adrenoreceptors, i. e. it is capable to inhibit the basal activity of these receptors shifting the equilibrium between active and nonactive conformations toward the last.